Multifractal Methods in Characterizing Pore Structure Heterogeneity During Hydrous Pyrolysis of Lacustrine Shale - Xiaofei Liang; Qinhong Hu; Xiugang Pu; Wei Li; Qiming Wang; Mengdi Sun; Wenzhong Han (Fractal and Fractional)
By using gas physisorption and multifractal theory, this study analyzes pore structure heterogeneity and influencing factors during thermal maturation of naturally immature but artificially matured shale from the Kongdian Formation after being subjected to hydrous pyrolysis from 250 °C to 425 °C. As thermal maturity increases, the transformation of organic matter, generation, retention, and expulsion of hydrocarbons, and formation of various pore types, lead to changes in pore structure heterogeneity. The entire process is divided into three stages: bitumen generation stage (250–300 °C), oil generation stage (325–375 °C), and oil cracking stage (400–425 °C). During the bitumen generation stage, retained hydrocarbons decrease total-pore and mesopore volumes. Fractal parameters ΔD indicative of pore connectivity shows little change, while Hurst exponent H values for pore structure heterogeneity drop significantly, indicating reduced pore connectivity due to bitumen clogging. During the peak oil generation stage, both ΔD and H values increase, indicating enhanced pore heterogeneity and connectivity due to the expulsion of retained hydrocarbons. In the oil cracking stage, ΔD increases significantly, and H value rises slowly, attributed to the generation of gaseous hydrocarbons further consuming retained hydrocarbons and organic matter, forming more small-diameter pores and increased pore heterogeneity. A strongly negative correlation between ΔD and retained hydrocarbon content, and a strongly positive correlation with gaseous hydrocarbon yield, highlight the dynamic interaction between hydrocarbon phases and pore structure evolution. This study overall provides valuable insights for petroleum generation, storage, and production.